1997
DOI: 10.1109/18.556118
|View full text |Cite
|
Sign up to set email alerts
|

Extended Ziv-Zakai lower bound for vector parameter estimation

Abstract: The Bayesian Ziv-Zakai bound on the mean square error (MSE) in estimating a uniformly distributed continuous random variable is extended for arbitrarily distributed continuous random vectors and for distortion functions other than MSE. The extended bound is evaluated for some representative problems in time-delay and bearing estimation. The resulting bounds have simple closed-form expressions, and closely predict the simulated performance of the maximum-likelihood estimator in all regions of operation. Index T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
175
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(178 citation statements)
references
References 33 publications
(72 reference statements)
2
175
0
Order By: Relevance
“…A detailed derivation of the Ziv-Zakai bound [24,58,59] is provided in Appendix B. The final result reads MSE(θ est ) µ,θ 0 ≥ ∆ 2 θ ZZB , where…”
Section: Ziv-zakai Boundmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed derivation of the Ziv-Zakai bound [24,58,59] is provided in Appendix B. The final result reads MSE(θ est ) µ,θ 0 ≥ ∆ 2 θ ZZB , where…”
Section: Ziv-zakai Boundmentioning
confidence: 99%
“…[24,58,59]). This Appendix follows these derivations closely and provides additional background, which may be useful for readers less familiar with the field of hypothesis testing.…”
Section: Appendix B Derivation Of the Ziv-zakai Boundmentioning
confidence: 99%
“…Once again, the GML solution is an affine transformation of the sample covariance matrix that, omitting constant terms, is given by Tr (10) with (11) which is the covariance matrix of . Therefore, bearing in mind that Tr , it is found that Tr (12) are the independent term and the kernel of the GML likelihood function (10), respectively.…”
Section: Gaussian Maximum Likelihood (Gml)mentioning
confidence: 99%
“…Further improvements have been made by Bellini & Tartara [4], and Weiss & Weinstein [5], [6]. Extension to the vector case has also been developed [7]. The improved ZZBs in [5], [6] are applicable to either narrowband or wideband waveforms because of explicit assumptions made throughout the derivations.…”
Section: Introductionmentioning
confidence: 99%